Mezlocillin and ticarcillin alone and combined with gentamicin in the treatment of experimental Enterobacter aerogenes endocarditis. - Levison, M E (1984)
The efficacies of mezlocillin and ticarcillin, each alone and in combination with gentamicin, in the therapy of experimental left-sided Enterobacter aerogenes endocarditis in rabbits were compared. Each beta-lactam was administered intramuscularly at a dose of 180 mg/kg every 6 h either alone or with gentamicin (1.7 mg/kg intramuscularly every 8 h). Bacterial populations at the start of therapy (7 days after initiation of infection) were 9 to 10 log10 CFU/g of vegetation. Ticarcillin produced concentrations in serum that were twice those produced by mezlocillin, but the therapeutic ratios of mezlocillin and ticarcillin (ratio of peak level in serum to MBC) were the same. All of the therapeutic regimens given for either 5 or 10 days were effective in reducing vegetation counts when compared with the untreated controls (P less than 0.01 for all comparisons), except mezlocillin alone and ticarcillin alone, which caused insignificant reductions in counts after 5 days of therapy (P greater than 0.05). After 10 days of therapy, the only regimen that was significantly different from another was that of mezlocillin plus gentamicin, which was significantly better than that of ticarcillin alone (P less than 0.01). These studies document that mezlocillin and ticarcillin were both effective in reducing the numbers of E. aerogenes CFU in vegetations in rabbits with experimental endocarditis when the drugs were given over a prolonged course. More rapid and extensive reduction in vegetation counts was achieved with combinations of an aminoglycoside plus mezlocillin or ticarcillin. Mortality was significantly less among rabbits treated with mezlocillin plus gentamicin.